Legal Review of Standard Inpatient Class Policy in Indonesia's National Health Insurance System - Nurvidyaning, Setyana Eka; Sanjaya, Kadek Edy Januar; Anggraeni, Happy Yulia (Research Horizon, 2025)
The national health insurance is a strategic initiative by the Indonesian government to guarantee equitable access to affordable and quality healthcare services for all citizens. Nevertheless, the program faces multiple challenges including financial sustainability, inadequate healthcare facilities and personnel, and policy inefficiencies. To enhance the quality of national health insurance implementation, the government introduced several policy reforms, one of which is the transformation of inpatient classification into a standardized scheme known as standard inpatient class. Standard inpatient class was formulated in response to the community's evolving healthcare needs and to replace the traditional tiered room system. Law No. 40 of 2004 on the national social security system affirms that all national health insurance participants are entitled to equitable, adequate, and non-discriminatory healthcare services, including fair access to inpatient facilities. The implementation of standard inpatient class is thus regarded as part of the state’s duty in fulfilling the human right to health. This policy is expected to positively impact both hospitals and patients, fostering a just, public-oriented, and rights-based healthcare system. With comprehensive reforms, national health insurance can continue to evolve into a fair, efficient, and sustainable health insurance system for all Indonesians.